Heinrich Rickert’s stand on the theory of reflection - Kubalica, Tomasz (Folia Philosophica, 2009)
The aim of the paper is to discuss primarily the epistemological theory of reflection (Abbildtheorie) as seen by Heinrich Rickert, the main representative of Neo-Kantianism Baden School. The most important arguments put forward by Rickert against taking the cognition as a reflection of the reality are being analysed. Rickert’s standpoint turns out to be moderate. He argues against the transcendental theory of reflection, but does not reject the idea of reflection as a model of cognition and takes the immanent theory of reflection as relatively justified. The paper contains also a discussion of the standpoint of another representative of Baden School, Emil Lask, who has rejected the theory of reflection in favour of the after-image theory (Nachbildtheorie).